Reactive, nonreactive, and flash spark plasma sintering of Al2O3/SiC composites—A comparative study. Issue 1 (30th August 2019) - Torosyan, Karen S.; Sedegov, Alexey S.; Kuskov, Kirill V.; Abedi, Mohammad; Arkhipov, Dmitry I.; Kiryukhantsev‐Korneev, Philipp V.; Vorotilo, Stepan; Moskovskikh, Dmitry O.; Mukasyan, Alexander S.
Abstract: The influence of different SPS‐based methods, that is, conventional spark plasma sintering (SPS), flash SPS (FSPS), and reactive SPS (RSPS) on the properties of Al2 O3 /SiC composite was investigated. It was shown that the application of preliminary high energy ball milling of the powders significantly enhances the sinterability of the ceramics. It was also demonstrated that FSPS provides unique conditions for rapid, that is, less than a minute, consolidation of refractory ceramics. The Al2 O3 ‐20 wt% SiC composite produced by FSPS possesses the highest relative density ( 99%), fracture toughness (7.5 MPa m 1/2 ), hardness (20.3 GPa) and wear resistance among all ceramics produced by other SPS‐based approaches with dwelling time 10 minutes. The RSPS ceramics hold the highest Young's modulus (390 GPa). Substitution of micron‐sized Al2 O3 particles by nano alumina does not lead to measurable enhancement of the mechanical properties.